VD_FINDINFO HC / 2012 / 255 vom 17. April 2012 - VD Tribunal cantonal (2012)
APPRÉCIATION DES PREUVES, COMPENSATION DE CRÉANCES, COURTIER, INTERDICTION DE L'ARBITRAIRE | 120 CO, 412 al. 1 CO, 413 al. 1 CO, 186 CPC, 9 Cst.